Primary Assessment of the Phenomena of Chemo-Brain Among Iraqi Cancer Patients - Alharganee, Anmar; Aljasmawi, Mokhalad A.; Tahreer, Harith A.; Abubakar, Zuleihat O.; Albeer, Raneem Laith (British Journal of Healthcare and Medical Research, 2024)
Survival rates increased substantially with adjuvant chemotherapy.